Undergraduate Nursing Students’ Knowledge, Attitude and Practice Toward Palliative Care in Indonesia: A Cross-sectional Online Survey - Agustini, Luh Putu Inca Buntari; Nursalam, Nursalam; Faridah, Virgianti Nur; Rismawan, Made (International Journal of Psychosocial Rehabilitation, 2020)
Confirming adequate knowledge about palliative care (PC) and positive attitudes towards PC are crucial educational aspects when arranging undergraduate nursing students to act on the complexities of care for people affected by a progressive, life-limiting illness. In Indonesia, the level of students’ attained knowledge and developed attitudes and practice towards PC remain unknown. The objective of this study was to investigate Indonesian undergraduate nursing students’ knowledge, attitude, and practice towards PC. A quantitative research method and descriptive online-survey design were used. The sample consisted of 240 undergraduate nursing students selected by using simple random sampling from three private nursing schools. Participants completed a demographic form, the Palliative Care Quiz for Nursing, the Frommelt Attitudes Towards Care of the Dying questionnaire, and a PC practice questionnaire. Of the total 255 participants selected, a response rate of 240 (94.2%) was achieved. Out of the total study participants, only 51 (24.3%) had good knowledge but 226 (94.2%) had a favorable attitude towards PC. Regarding the knowledge aspect of the practice, the majority of the respondents 198 (85.2%) had good implementation. Currently, the students widely held a lack of knowledge, but their attitude and knowledge aspect of practice towards PC was favorable. Thus, assimilating PC education by developing an effective learning model for nursing students to improve knowledge is critical.